Model Kelembagaan Pengelolaan Teknologi Mikrohidro Berbasis Masyarakat (Studi Kasus : Desa Gunung Lurah Kecamatan Cilongok Kabupaten Banyumas) - Kusdariyanto, Irwan (Jurnal Sosial Ekonomi Pekerjaan Umum, 2013)
In some developing countries, development activities are concentrated in urban areas in which facilities support it. On the other hand, development in rural areas is relatively slow due to lack of infrastructure and facilities. Energy, particularly electricity, is one of basic infrastructure needed to improve quality of life and economic growth in the rural areas. This paper attempts to develop a micro-hydro technology management model, based on the stages of institutional establishment by the technology user group. The stages are derived from model test theory (Borg and Gall, 1989) and developed to ten main steps. This research utilizes qualitative method incorporated with quantitative method. The result indicates that the user group in case study location followed the stages model although some modifications are applied. It shows that the model is quite applicable in managing community-based institution of micro-hydro technology development.